2018
DOI: 10.1371/journal.pgen.1007652
|View full text |Cite
|
Sign up to set email alerts
|

Robust activation of microhomology-mediated end joining for precision gene editing applications

Abstract: One key problem in precision genome editing is the unpredictable plurality of sequence outcomes at the site of targeted DNA double stranded breaks (DSBs). This is due to the typical activation of the versatile Non-homologous End Joining (NHEJ) pathway. Such unpredictability limits the utility of somatic gene editing for applications including gene therapy and functional genomics. For germline editing work, the accurate reproduction of the identical alleles using NHEJ is a labor intensive process. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 37 publications
4
87
0
Order By: Relevance
“…We and others (15,16,19) have shown that DSBs directed at sites likely to be repaired via MMEJ significantly increase the homogeneity of the resulting repair outcomes in zebrafish. Despite there being no known clear biochemical mechanism as to how MMEJ repairs DSBs, we and others (20)(21)(22)(23) have published software tools that predict the occurrence of MMEJ based on the sequence context surrounding any given target DSB site.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…We and others (15,16,19) have shown that DSBs directed at sites likely to be repaired via MMEJ significantly increase the homogeneity of the resulting repair outcomes in zebrafish. Despite there being no known clear biochemical mechanism as to how MMEJ repairs DSBs, we and others (20)(21)(22)(23) have published software tools that predict the occurrence of MMEJ based on the sequence context surrounding any given target DSB site.…”
Section: Introductionmentioning
confidence: 82%
“…This deletion pattern is then useful as a heuristic to identify probable MMEJbased repairs from a mixed-repair pool. The ability to generate predictable genotypes (14), sometimes even resulting in an identical allele in over half of the editing outcomes (15), makes MMEJ an attractive alternative to NHEJ for precision genome engineering (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early zebrafish embryo, microhomology mediated end joining (MMEJ) is an active DNA repair pathway that generates predictable alleles after nuclease targeting (Thyme and Schier 2016) (He et al 2015) (Ata et al 2018). MMEJ-based gene editing has been described in zebrafish and mammalian cells, though the homology arms used for these events may be more similar in length to those employed in Single Strand Annealing (SSA) (Aida et al 2016) (Hisano et al 2015) (Nakade et al 2014) (Bhargava, Onyango, and Stark 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In organisms such as silkworm and zebrafish, the MMEJ-mediated integration of 417 fluorescent marker genes with TALEN and CRISPR/Cas9 system has been successful 418 (Nakade et al 2014;Ata et al 2018). Therefore, we attempted to generate knock-in yeast 419 cells using the MMEJ-mediated CRISPR/Cas9 system.…”
mentioning
confidence: 99%